2021
DOI: 10.1016/j.jand.2020.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics in Conditions or Infections Similar to COVID-19 on Health Outcomes: An Evidence Analysis Center Scoping Review

Abstract: Probiotics have been suggested as a potential intervention for improving outcomes, particularly ventilatory-associated pneumonia, in patients infected with coronavirus disease 2019 (COVID-19). However, with the rapid development of the COVID-19 pandemic, there is little direct evidence available in infected patients. The objective of this scoping review is to examine the availability and nature of literature describing the effect of probiotics in adults with conditions or infections similar to COVID-19 infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
(250 reference statements)
0
14
0
1
Order By: Relevance
“…Although, most of the findings suggest that SARS-Cov-2 virus is more likely transmitted through the respiratory route, but many data also suggest that the intestine could play an appropriate role in the pathogenetic evolution of this viral disease [23]. Rozga et al (2020), in a review study suggested probiotics may improve clinical symptoms such as ventilator-associated pneumonia in patients infected with SARS-Cov-2 [25]. Although, further researches are needed to identify the mechanisms for our finding and assess the effect of yogurt and doogh on the subject at risk of COVID-19, it is safe and secure to advise that high risk population for COVID19, consume enough amount of yogurt and doogh at the time of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Although, most of the findings suggest that SARS-Cov-2 virus is more likely transmitted through the respiratory route, but many data also suggest that the intestine could play an appropriate role in the pathogenetic evolution of this viral disease [23]. Rozga et al (2020), in a review study suggested probiotics may improve clinical symptoms such as ventilator-associated pneumonia in patients infected with SARS-Cov-2 [25]. Although, further researches are needed to identify the mechanisms for our finding and assess the effect of yogurt and doogh on the subject at risk of COVID-19, it is safe and secure to advise that high risk population for COVID19, consume enough amount of yogurt and doogh at the time of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral mechanism of fermented foods is not well known due to the limited clinical studies documented the daily intake for long term ( Aslam et al, 2020 ). On the other hand, the mechanism of probiotics has been established via several well designed clinical studies that recommended the required doses per day ( Rozga, M., Cheng, F. W., & Handu, 2020 ; King, Glanville, Sanders, Fitzgerald, & Varley, 2014 ; Reid, Jass, Sebulsky, & McCormick, 2003 ). Influenza virus is one of the common viruses that can cause serious respiratory tract infection and lead to high morbidity and mortality especially during influenza epidemics ( Taubenberger & Morens, 2008 ).…”
Section: Antiviral Activity Of Fermented Foods and Their Probioticsmentioning
confidence: 99%
“…Regarding probiotic and/or symbiotic (the latter is the addition of prebiotics to probiotics) supplementation and treatment, no primary research is available for COVID-19 or other coronaviruses-affected patients with mild to moderate symptoms [ 93 ]. A recent review addressed the role of probiotics as an adjuvant therapy in COVID-19 infection and other viral and inflammatory diseases [ 94 ].…”
Section: Microbiomementioning
confidence: 99%
“…Some evidence exists for the positive outcomes of symbiotic treatments in other critically ill patients on mechanical ventilators and with severe pulmonary diseases. There are also some clinical trials in COVID-19 patients currently underway which might soon provide more insight into the issue [ 93 ]. The lack of evidence is of no surprise not just because of the novelty of some coronaviruses but also due to the complex actions of both pro- and prebiotics regarding their viability, specificity (strain/substrate), dose, and duration in the context of providing possible beneficial immunologic, metabolic and protective effects [ 94 ].…”
Section: Microbiomementioning
confidence: 99%